Stigma as a Barrier to Mental Health Service Use Among Female Sex Workers in Switzerland - Zehnder, Mara; Mutschler, Jochen; Rössler, Wulf; Rufer, Michael; Rüsch, Nicolas (Frontiers in Psychiatry, 2019)
Background: Many sex workers suffer from mental health problems, but do not seek help. Aim: To examine stigma-related and non stigma-related barriers to care and perceived need for treatment among female sex workers in Switzerland. Methods: Mental health service use, barriers to care, perceived need and presence of illness, symptoms, and psychiatric diagnoses were assessed among 60 female sex workers in Zürich, Switzerland. Outcomes: Mental health service use was defined as use of psychiatric medication, psychotherapy, or substance use services for at least 1 month during the past 6 months. Results: Adjusting for symptom levels, mental health service use was predicted by lower stigma-related, not by structural, barriers as well as by more perceived need for treatment and higher age. Clinical Implications: Sex workers with mental health problems would benefit from non-stigmatizing mental health care as well as from interventions to reduce public and self-stigma associated with mental illness and sex work. Strengths and Limitations: Limitations are the cross-sectional data, limited sample size, and recruitment from an information center for sex workers. Conclusion: Interventions that aim to increase mental health service use among sex workers should take stigma variables into account.